(untitled) - Thích Thiền Tâm (New York, 1994)
The primary focus of this treatise is Pure Land theory and practice. This notwithstanding, more than half of the book is devoted to questions of concern to all Buddhist schools. Therefore, we suggest the following approach to reading the text, accordung to the background of the reader
Keywords: Phật giáo,Buddhism; Thánh kinh,Trích dẫn,Sacred books,Quotations